An Efficient Disassembly Sequencing Scheme Using the Shell Structure. (January 2023) - Rehal, Arun; Sen, Dibakar
Abstract: This paper presents a part accessibility-based assembly partitioning scheme for efficient disassembly sequence planning. Accessibility of parts is shown to be an important consideration in product Disassembly Sequence Planning (DSP), which in turn has applications in Assembly Planning (AP), Maintenance Planning (MP), and End-of-Life (EOL) processing. A substantial amount of research exists on both DSP and MP . However, accessibility analysis of parts in an assembly remains largely unexplored. In this paper, we introduce the notion of shell structures associated with 3D CAD assemblies for accessibility analysis of parts. The proposed approach classifies the surface domains of parts as mating or non-mating domains. The non-mating domains are used to construct the shell structure, and the mating domains are used to generate the liaison information of the assembly. The method requires only one-time computation of the shells; throughout the disassembly process, the accessibility information in the shells is updated without any recomputation. Further applications of shell structures, such as in subassembly identification and parallel disassembly, which are important for maintenance planning and end-of-life processing, are also demonstrated. We propose a grid-based method for constructing the shell structure from the tessellated model of the assembly. Finally, results obtained for tessellated models demonstrate the efficacy of the proposed methods. The results show that the accessibility assessment can be done in very little time using the proposed approach. The dynamic update of shells after each disassembly operation results in efficient updating of accessibility information. Highlights: Assembly partitioning scheme for efficient Disassembly Sequence Planning (DSP). Partitioning is achieved by the accessibility-based grouping of parts. Shell Structures are introduced for accessibility analysis of parts. Shell Structures are shown to be useful for Subassembly Identification also. Accessibility analysis can be done in very little time using shell structures.